IMPLEMENTASI PERATURAN MENTERI KEHUTANAN NOMOR P.75/MENHUT-II/2014 TENTANG POLISI KEHUTANAN DALAM MENCEGAH KERUSAKAN HUTAN TINJAUAN FIKIH SIYASAH: IMPLEMENTATION OF FORESTRY MINISTER REGULATION NUMBER P.75/MENHUT-II/2014 CONCERNING FORESTRY POLICE IN PREVENTING FOREST DAMAGE FIKIH SIYASAH REVIEW - Aulia Mayasari; Gani Jumat (Qaumiyyah: Jurnal Hukum Tata Negara, 2023)
Forest protection is a very important activity because the facts show that forest destruction in Indonesia has reached a very worrying level. Therefore, it is very appropriate for the government to pay attention to forest protection. The Forestry Police, as the front guard in guarding forests based on the Regulation of the Minister of Forestry Number P.75/Menhut-II/2014, has the task and function of carrying out the protection and security of forests, forest areas, and forest products. Of course, forest damage will not occur if the Forestry Police carry out their duties and functions well. The description in this thesis departs from the problem of how to implement Regulation of the Minister of Forestry Number P.75/Menhut-II/2014 concerning Forestry Police in preventing damage to the Lore Lindu National Park Forest? and how is the Siyasah Fikih Review of the Implementation of the Regulation of the Minister of Forestry Number P.75/Menhut-II/2014 Concerning Forestry Police in preventing forest damage in Lore Lindu National Park? This research uses an empirical judicial approach and data collection techniques through observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. From the research results, it was concluded that the Forestry Police, especially in the Lore Lindu National Park Forest, had carried out their duties in accordance with the Regulation of the Minister of Forestry Number P.75/Menhut-II/2014 through preemptive, preventive, and repressive activities. These three steps have been carried out. However, there are still several obstacles faced in the field, such as a lack of personnel, difficult terrain to traverse, and economic problems in the community, which also influence the success of the duties of the Forestry Police themselves. Regulation of the Minister of Forestry Number P.75/Menhut-II/2014, In an effort to carry out their duties and functions, the Forestry Police also provide education and invite the public to work together to preserve nature. Judging from the Siyasah Fikih, the duties of the Forestry Police are in accordance with the principles of the Siyasah Fikih, which include the principles of human position on earth, leadership, commanding good and evil, responsibility of the leader, and obedience of the people. Abstrak Perlindungan Hutan merupakan suatu kegiatan yang sangat penting karena fakta menunjukkan bahwa, kerusakan hutan di Indonesia telah masuk pada skala yang sangat mengkhawatirkan, karenanya sangat pantas apabila pemerintah menaruh perhatian terhadap perlindungan hutan. Polisi Kehutanan sebagai garda terdepan dalam penjagaan hutan berdasarkan aturan Peraturan Menteri Kehutanan Nomor P.75/Menhut-II/2014 mempunyai tugas dan fungsi melaksanakan perlindungan dan pengamanan hutan, kawasan hutan, dan hasil hutan. Tentunya kerusakan hutan tidak akan terjadi apabila Polisi Kehutanan melaksanakan tugas dan fungsinya dengan baik. Uraian dalam skrispsi ini berangkat dari masalah bagaimana Implementasi Peraturan Menteri Kehutanan Nomor P.75/Menhut-II/2014 tentang Polisi Kehutanan dalam mencegah kerusakan Hutan Taman Nasional Lore Lindu?, dan bagaimana Tinjauan Fikih Siyasah terhadap Implementasi Peraturan Menteri Kehutanan Nomor P.75/Menhut-II/2014 Tentang Polisi Kehutanan dalam menecegah kerusakan hutan Taman Nasional Lore Lindu. Penelitian ini menggunakan pendekatan Yuridis Empiris, teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi, teknik analisis data yang digunakan adalah reduksai data, penyajian data, dan verifikasi data. Dari hasil penelitian, menyimpulkan Polisi Kehutanan khususnya di Hutan Taman Nasional Lore Lindu telah melaksanakan tugas sesuai dengan Peraturan Menteri Kehutanan Nomor P.75/Menhut-II/2014 melalui kegiatan preemtif, preventif dan represif. Adapaun ketiga langkah tersebut telah dilakukan. Namun, masih ditemukan beberapa kendala yang dihadapi di lapangan seperti kurangnya personil, sulitnya medan yang dilalui dan permasalahan ekonomi masyarakat yang turut mempengaruhi keberhasilan tugas dari Polisi Kehutanan itu sendiri Polisi Kehutanan merupakan pelaksana aturan yang memiliki tugas dan kewajiban untuk menjaga dan melindungi hutan sesuai amanat Peraturan Menteri Kehutanan Nomor P.75/Menhut-II/2014, Dalam upaya menjalankan tugas dan fungsinya, Polisi Kehutanan juga memberikan penyuluhan dan mengajak masyarakat untuk bersama-sama menjaga kelestarian alam. Ditinjau berdasarkan Fikih Siyasah mengenai tugas-tugas Polisi Kehutanan tersebut telah sesuai dengan prinsip- prinsip Fikih Siyasah yang meliputi prinsip kedudukan manusia dimuka bumi, kepemimpinan, amar ma’ruf nahi mungkar, tanggung jawab pemimpin, dan ketaatan umat.